Memorable media messages of mental illness and implications for policy support: examining the influences of racial ingroup/outgroup recall - Riles, Julius Matthew; Adediran, Abigail; Akheituame, Esther; Madrigal, Guadalupe; Behm-Morawitz, Elizabeth (Frontiers in Psychology, 2025)
IntroductionIt is vital to understand how memorable media representations of mental illness influence perceptions about, and policies affecting, people managing mental illness.MethodUtilizing an experiment, this study empirically examines how ingroup/outgroup racial identity recall of those managing mental health conditions may condition respondents' perceptions of mental illness more broadly, including support for allocating mental health resources.ResultsFindings suggest that the ingroup/outgroup racial identity recall of a memorable media message significantly predicts broader culpability judgments of people managing mental illness and support for mental health-related policies. Unexpectedly, memorable media message recall of racial outgroups was associated with less perceived culpability for a mental illness than recall of racial ingroups. However, content analysis of the recalled messages reveals that, among other cues, explicit emphasis of race, negative language, and perceived potential for messages to influence audiences were most pronounced during recall of racial outgroups with mental illnesses than recall of racial ingroups.DiscussionImplications of patterns for health disparity support for mental illness, as well as mediated memorable message research are discussed.